(untitled) - Pinedo, Michael L. (Dordrecht, 2009)
This book focuses on planning and scheduling applications. Planning and scheduling are forms of decision-making that play an important role in most manufacturing and services industries. The planning and scheduling functions in a company typically use analytical techniques and heuristic methods to allocate its limited resources to the activities that have to be done." "This book is suitable for more advanced students in industrial engineering and operations research as well as graduate students in business.
Keywords: Kế hoạch sản xuất,Production planning